Investor and Manager Overconfidence Bias and Firm Value: Micro-Level Evidence from the Pakistan Equity Market - Shah, Sayyed Sadaqat Hussain; Xinping, Xia; Khan, Muhammad Asif; Harjan, Sinan Abdullah (International Journal of Economics and Financial Issues, 2018)
This study examines the effect of investor and manager overconfidence bias on firm value of dynamic panel of 432 firms listed at Pakistan Stock Exchange. To the best of our knowledge, this is the first effort that contemplates the micro-level dataset in context of an emerging economy spanning from 2013 to 2017. The empirical findings reveal that overconfident investors in Pakistan stock market positively and significantly drive the firm value. However, overconfident manager bias lacks the precise direction in explaining the firm value. These findings are consistent with literature that firms with overconfident investors and managers are characterized by high profitability, cash flows and prefer to use debt financing. Although the findings of the study are robust at the firm level, yet it is difficult to generalize the outcome of the single study, therefore much more to be explored in this context. Keywords: investor overconfidence bias, manager overconfidence bias, firm value JEL Classifications: G20, G11, G32